A design of HTM spatial pooler for face recognition using memristor-CMOS hybrid circuits - Ibrayev, Timur; James, Alex Pappachen; Merkel, Cory; Kudithipudi, Dhireesha (Institute of Electrical and Electronics Engineers Inc., 2016)
Hierarchical Temporal Memory (HTM) is a machine learning algorithm that is inspired from the working principles of the neocortex, capable of learning, inference, and prediction for bit-encoded inputs. Spatial pooler is an integral part of HTM that is capable of learning and classifying visual data such as objects in images.
Keywords: feature extraction; Hierarchical Temporal Memory; machine learning; memristor; neuromorphic design; pattern recognition; Research Subject Categories::TECHNOLOGY::Engineering physics